Sypialnia Art Deco ze zbiorów Muzeum Historycznego m. Krakowa. Uwagi o meblach i stylu wnętrz lat dwudziestych (Krzysztofory. Zeszyty Naukowe Muzeum Historycznego Miasta Krakowa, 2026)
AN ART DECO BEDROOM IN THE COLLECTION OF THE HISTORICAL MUSEUM IN CRACOW. SOME REMARKS ON FURNITURE AND INTERIOR STYLE OF THE 1920SThe article An Art Deco Bedroom in the Collection of the Historical Museum in Cracow. Some Remarks on the Furniture and Interior Style of the 1920s, is an attempt at determining a role and contribution of Polish designers in the development of European cabinet-making and designing in the first half of the 20th century. The publication was arranged to best serve that purpose. It covers a short history of the style together with characteristics of various trends within the style, the achievements of modern decorative art at the Paris Exhibition of 1925, Polish artists’ contribution to the formation of a new aesthetics in applied art, and finally, the history of the Polish type of the Art Deco, followed by a description of a set of furniture from the Historical Museum collection. The article shows different possibilities of dating the style with reference to its aesthetic origins. It presents different criteria that may be applied. The idea of functionalism and simplification allows to use as reference the precursory achievements of Thonet (following le Corbusier); a sort of ‘historism’ in the ‘high’ Arto Deco reminds the eclectic style od the 19th century. Despite the fact that the symbolic beginning of the style is 1907, the date on which Picasso completed his Maids of Avignon, the article shows that many cabinet-makers consciously continued the Neo-romantic aesthetics and the manufacturing techniques developed at the turn of the 19th century along with team work methods characteristic of modern furniture making in the 1920s. This view applies especially well to the Polish version of the Art Deco which may be treated as natural continuation of the achievements of modernist artists — Stanislaw Wyspiański and Karol Tichy. Referring to folk and historic art the artists were seeking an archetypical model of decorative art. That created excellent climate for adopting the ideas of futurism and cubism. The article presents a thesis that Polish modernists’ ideas were innovative and independent. Their striving for simplification of the object, their conscious use of contrast between the furniture and the background, a trend toward making decorations more abstract, and their care for the interior dynamics based on contrasts between horizontal and vertical lines and dark and light areas, were the artists’ contribution to art. However, this issue requires separate research and more in-depth study. Now it can be stated, however, that the Polish Art Deco at its early stage developed as a separate trend in cabinet-making, at least equivalent to such phenomena as Wiener Werkstatte or Deutsche Werkbund. This situation brought high appreciation from critics, and prizes awarded to Polish artists at the Paris Exhibition in 1925. The article also answers why Polish decorative art, with such splendid prospects for future, was left aside. Despite its genuine values it did not have an impact on European furniture designing, and remained perhaps not marginal, but virtually unknown. That was caused by the lack of capital investment or government support, needed to compete with well known French and German companies, and later by the world economic crisis.A separate subject of the article is the presentation of the development of modern aesthetics in decorative art. The author refers to the creation of such artistic groups as the English Arts and Crafts, through Wiener Werkstatte, Deutsche Werkbund, De Stijl and French furniture manufacturers, to Bauhaus and the early constructivism; in Poland it refers to the achievements of modernist artists associated in the Polish Applied Art Society in Cracow, then to Cracow Workshops, the Ład Cooperative and the W. Nowakowski’s firm in Poznań. The article describes the bedroom in detail, including proportions, decorations, kind of wood used, manufacturing techniques, and finally, which is the most important, a reconstruction of the bed’s original outlook. The set of furniture has been remodelled, which changed its original form. However, it seems a good idea to place this particular set of furniture in a separate room in an intended interior branch of the Cracow Historical Museum; the room should be arranged according to Polish design from that time, to strengthen the effect. The set is dated by the author to the late 1920’s (1926/27-1929), at the peak of the development of the Art Deco in Poland. The author also characterizes outstanding French designers, including Ruhlmann, Sue, Mare, and Leleu. This is so, because the presented set of furniture is clussified as a „high” Art Deco, and its originality is demonstrated using criteria similar to those applied in Western Europe, based on homogeneity of the interior aesthetics.Therefore the article is a proposal to undertake comprehensive research on dispersed Polish furniture from the first half of the 20th century.